2012
DOI: 10.1159/000340056
|View full text |Cite
|
Sign up to set email alerts
|

Randomized, Double-Blind, Parallel-Group, 48-Week Study for Efficacy and Safety of a Higher-Dose Rivastigmine Patch (15 vs. 10 cm2) in Alzheimer’s Disease

Abstract: Aim: Determine whether patients with Alzheimer’s disease demonstrating functional and cognitive decline, following 24–48 weeks of open-label treatment with 9.5 mg/24 h (10 cm2) rivastigmine patch, benefit from a dose increase in a double-blind (DB) comparative trial of two patch doses. Methods: Patients meeting prespecified decline criteria were randomized to receive 9.5 or 13.3 mg/24 h (15 cm2) patch during a 48-week, DB phase. Coprimary outcomes were change from baseline to week 48 on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
105
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 89 publications
(114 citation statements)
references
References 32 publications
7
105
0
2
Order By: Relevance
“…Safety results appeared to be broadly consistent with those previously reported with the 13.3 mg/24 h patch in patients with mild-to-moderate AD, 8 AEs, adverse events; N, number of patients in the population; n, number of patients reporting SAE, death or discontinuation; SAE, serious adverse event.…”
Section: Resultssupporting
confidence: 85%
See 4 more Smart Citations
“…Safety results appeared to be broadly consistent with those previously reported with the 13.3 mg/24 h patch in patients with mild-to-moderate AD, 8 AEs, adverse events; N, number of patients in the population; n, number of patients reporting SAE, death or discontinuation; SAE, serious adverse event.…”
Section: Resultssupporting
confidence: 85%
“…5,20 In the DB OPTIMA trial, GI AEs were more frequently reported in patients up-titrated from 9.5 mg/24 h to 13.3 mg/24 h patch than for patients continuing on 9.5 mg/24 h patch. 8 Likewise, in the DB ACTION study the incidence of GI AEs was higher in patients receiving 13.3 mg/24 h compared with 4.6 mg/24 h patch (nausea: 6.2% versus 2.8%; vomiting 7.0% versus 2.5%; diarrhea: 6.5% versus 5.3%, respectively). 9 It is also now recommended that patients receive 9.5 mg/24 h patch for a minimum of 4 weeks before up-titrating to the 13.3 mg/24 h patch dose.…”
mentioning
confidence: 92%
See 3 more Smart Citations